Zeolite modified porous drug-loaded slow-release nanofiber and preparation method thereof

By wrapping zeolites in nanofibers and using the combination of polymer materials to form a porous structure, the shortcomings of existing nanofiber drug-loaded sustained-release preparations in terms of drug loading, release rate and stability are solved, and the uniform distribution and effective sustained-release of drugs are achieved, extending the sustained-release time and improving the absorption effect of drugs.

CN119896749APending Publication Date: 2025-04-29SHAOYANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510091343.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing nanofiber drug-loaded sustained-release preparations have shortcomings in drug loading, drug release rate and stability, and it is difficult to ensure the uniform distribution and effective release of drugs in the fiber.

Method used

The zeolite is used as the carrier material, and the zeolite is uniformly wrapped inside the nanofibers by electrospinning, and a combination of hydrophilic and hydrophobic polymer materials is used to form a porous structure to coordinate the sustained release of the drug.

Benefits of technology

Through various release pathways (hydrophilic polymer dissolution release, zeolite surface diffusion release, and mesoporous slow release), the sustained release time of water-soluble drugs is effectively extended, the absorption effect and utilization of drugs are improved, and the biodegradability and biocompatibility of the preparation are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896749A_ABST
    Figure CN119896749A_ABST
Patent Text Reader

Abstract

The invention discloses a zeolite modified porous drug-loaded slow-release nanofiber and a preparation method thereof. The zeolite modified porous drug-loaded slow-release nanofiber is prepared from zeolite, a water-soluble drug and a nanofiber with a uniform porous structure, wherein the zeolite is wrapped in the nanofiber, and the water-soluble medicine is loaded in mesopores of the zeolite, on the surface of the zeolite and in the nanofiber; the nanofiber comprises a hydrophilic high polymer material and a hydrophobic high polymer material. According to the material, the uniformly distributed porous structures cooperate with the zeolite material wrapped by the nanofiber and the nanofiber co-constructed by the hydrophilic high-molecular material and the hydrophobic high-molecular material, so that multiple ways are provided for the release of the water-soluble medicine, and the slow release time and the utilization rate of the medicine in a body can be effectively improved. In addition, the material has good biodegradability and biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and specifically relates to a zeolite-modified porous drug-loaded sustained-release nanofiber and a preparation method thereof. Background Art

[0002] Some drugs have a short half-life in the body and need to be administered frequently to maintain effective concentrations, but frequent administration may cause inconvenience to patients and decreased compliance. Taking diclofenac sodium as an example, ordinary diclofenac sodium tablets need to be taken 2 to 3 times a day. If the single dose is too high, it may induce serious gastrointestinal adverse reactions, including upper abdominal discomfort, gastrointestinal bleeding, decreased urine volume, physical weakness, loss of appetite and skin rash. On the other hand, if side effects are avoided by reducing the single dose and increasing the frequency of medication, it often leads to frequent problems such as missing or forgetting to take medication.

[0003] Sustained-release preparations use specific technology to release drugs at a slow and non-uniform rate in a specified release environment, aiming to prolong the efficacy of the drug, reduce the frequency of medication, and effectively reduce the toxicity and side effects of the drug. Therefore, developing such drugs into sustained-release dosage forms can not only reduce the frequency of medication, but also effectively prevent the sudden release of large amounts of drugs and maintain a stable drug concentration in the blood, thereby meeting patients' needs for reducing toxic side effects and enhancing the reliability and sustainability of drug treatment.

[0004] Electrospinning is an effective method for preparing nanofibers, which can produce fibers with high specific surface area, good pore structure and controllable morphology. These characteristics make nanofibers prepared by electrospinning an ideal drug sustained-release carrier. However, the drug sustained-release carriers prepared by electrospinning still need to be further optimized in terms of drug loading, drug release rate and stability. In addition, how to ensure the uniform distribution and effective release of drugs in the fibers is also a technical challenge currently faced.

[0005] Zeolite is a natural porous mineral with excellent adsorption and ion exchange capabilities. Its porous structure enables zeolite to be used as a carrier material to effectively load drugs and control the release rate of drugs by adjusting the pore size and distribution. However, there are currently no reports on the use of zeolite to achieve sustained drug release using electrospinning. Summary of the invention

[0006] In view of the shortcomings of the prior art nanofiber drug-loaded sustained-release preparations, the first object of the present invention is to provide a zeolite-modified porous drug-loaded sustained-release nanofiber, which utilizes a uniformly distributed porous structure to cooperate with the zeolite material wrapped inside the nanofiber and the nanofibers constructed by the hydrophilic polymer material and the hydrophobic polymer material, providing multiple pathways for the release of water-soluble drugs, and can effectively improve the sustained-release time and absorption effect of the drug in the organism. In addition, the material has good biodegradability and biocompatibility.

[0007] The second object of the present invention is to provide a method for preparing zeolite-modified porous drug-loaded sustained-release nanofibers. This method uses zeolite as a carrier material combined with electrospinning to evenly wrap the drug-loaded zeolite inside the nanofibers, and the introduction of zeolite during the spinning process will form a uniformly distributed pore structure on the surface of the nanofibers.

[0008] In order to achieve the above technical objectives, the present invention provides a zeolite-modified porous drug-loaded sustained-release nanofiber, which is composed of zeolite, water-soluble drugs and nanofibers with a porous structure; wherein the zeolite is wrapped inside the nanofibers, and the water-soluble drugs are loaded in the mesopores of the zeolite and on its surface and inside the nanofibers; the nanofibers include hydrophilic polymer materials and hydrophobic polymer materials.

[0009] The technical solution of the present invention provides multiple pathways for the release of water-soluble drugs through the synergistic effect of structure and components. Specifically, first, the water-soluble drugs dispersed inside the nanofibers are quickly released through the dissolution of hydrophilic polymers; then, the water-soluble drugs adsorbed on the surface of the zeolite slowly diffuse out through the evenly distributed pore structure of the nanofibers; finally, the water-soluble drugs adsorbed in the mesopores of the zeolite are released from the mesopores and slowly released along the porous structure. Through the combination of these three sustained-release pathways, the sustained-release time of the water-soluble drugs is effectively improved and extended. At the same time, due to the introduction of zeolite, while ensuring the good biodegradability and biocompatibility of the sustained-release preparation (i.e., sustained-release nanofibers), the sustained-release time and drug utilization rate of the sustained-release preparation are effectively improved, and the absorption effect of the drug in the body is improved.

[0010] In addition, the composition of nanofibers is another key control factor to ensure the structural integrity and sustained release effect of sustained-release preparations. The inventors found that hydrophilic polymer materials have good solubility in sustained-release solutions, and can release part of the drug after dissolving. However, if all hydrophilic polymers are used as nanofiber components, it will cause a sudden release of the drug and fail to achieve a sustained-release effect; while hydrophobic polymers as the skeleton cannot dissolve in the sustained-release solution, which prolongs the sustained-release time of the drug. However, if all hydrophobic polymers are used, the drug is completely coated in the nanofibers and is difficult to release, resulting in low drug utilization.

[0011] As a preferred solution, the pore size of the porous structure on the surface of the nanofiber is in the range of 10 to 200 nm. The pore size on the nanofiber within this range is conducive to the diffusion of the internal drug and intercepts the zeolite particles inside the fiber so that they are not completely exposed to the sustained-release solution, ensuring the existence of the third sustained-release pathway.

[0012] The zeolite material selected in the present invention can achieve the sustained release effect of the present invention as long as it has a mesoporous structure, and is more preferably stellerite with mesopores and good biocompatibility and stability.

[0013] The present invention also provides a method for preparing zeolite-modified porous drug-loaded sustained-release nanofibers, the method comprising the following steps:

[0014] 1) dispersing a water-soluble drug and zeolite in water and then mixing and stirring until the water is completely volatilized to obtain drug-loaded zeolite powder; the zeolite has a mesoporous structure;

[0015] 2) dissolving a hydrophilic polymer material and a hydrophobic polymer material in a solvent and mixing the solvent with drug-loaded zeolite powder to obtain a spinning solution;

[0016] 3) Absorb the spinning solution for electrostatic spinning, and then dry it to obtain the product.

[0017] The present invention first uses zeolite as a carrier to load the drug on its mesoporous structure and the surface of the zeolite. Then, it is mixed and dispersed with a hydrophilic polymer material and a hydrophobic polymer material, and part of the drug on the surface of the zeolite is dissolved in the polymer solution, thereby forming a uniformly dispersed spinning solution. By electrostatic spinning, the zeolite can be uniformly wrapped in the nanofiber, and part of the drug is uniformly dispersed inside the nanofiber. At the same time, the present invention uses dichloromethane or chloroform and water as solvents during the preparation process to form a polymer / solvent / non-solvent ternary system, and non-solvent induced phase separation occurs. During the spinning process, the volatilization of the volatile solvent-dichloromethane or chloroform can form a porous structure on the shallow surface of the nanofiber. During the drying process, the non-volatile non-solvent-water adsorbed in the zeolite mesopores further volatilizes, so that a deeper and uniform porous structure is formed on the surface of the nanofiber, which is conducive to the release of the drug.

[0018] As a preferred solution, the water-soluble drug includes any one of diclofenac sodium and sodium valproate.

[0019] As a preferred solution, the mass ratio of the water-soluble drug to the zeolite is 1:(1-5). As the amount of zeolite increases, the pore size and diameter of the drug-loaded nanofibers increase, but at the same time, the uniformity of the pore size of the nanofibers will decrease. In the early stage of release, since the drug inside the nanofibers is mainly released, the increase in the amount of zeolite has little effect on the early release rate. In the middle and late stages of sustained release, as the amount of zeolite increases, the drug loaded on the zeolite surface and mesopores will decrease accordingly, so the release rate and cumulative release will decrease at the beginning of the middle stage of sustained release as the amount of zeolite increases; but when the zeolite increases to a certain extent, the pore size on the nanofibers will increase, so the release rate and cumulative release will tend to increase again.

[0020] More preferably, the mass ratio of the water-soluble drug to the zeolite is 1:(1-3); even more preferably, the mass ratio of the water-soluble drug to the zeolite is 1:(1-2).

[0021] As a preferred solution, the particle size of the zeolite is 1250-10000 mesh. In the present invention, the particle size of the zeolite has a direct impact on the diameter and pore size of the nanofibers. As the particle size of the zeolite decreases, the diameter and pore size of the nanofibers are significantly reduced, thereby affecting the early and mid-late release rates of the drug. It is further preferred that the particle size of the zeolite is 4000-5000 mesh.

[0022] As a preferred solution, the mass concentration of the drug-loaded zeolite powder in the spinning solution is 2-5%. Since stellerite has many mesoporous structures inside, loading the drug on the zeolite first and then performing electrostatic spinning can effectively prolong the sustained release time of the drug.

[0023] As a preferred solution, in step 1), the temperature of the mixing and stirring is 50-90° C. Within the temperature range selected in the present invention, sufficient loading of zeolite and water-soluble drugs can be ensured.

[0024] As a preferred solution, the total mass concentration of the hydrophilic polymer material and the hydrophobic polymer material in the spinning solution is 8-12%.

[0025] As a preferred solution, the hydrophilic polymer material includes at least one of PVP and PVA; the hydrophobic polymer material includes at least one of PLA and PCL.

[0026] As a preferred solution, the mass ratio of the hydrophobic polymer material to the hydrophilic polymer material is (10-1):1. The mass ratio of the hydrophobic polymer material to the hydrophilic polymer material in the spinning solution of the present invention directly affects the later release rate of the sustained-release preparation; as the amount of hydrophilic polymer material increases, the wrapped fiber is easier to dissolve in water, and the drug is easier to release in the same time. If the proportion of hydrophobic polymers in the spinning solution is too large and the proportion of hydrophilic polymers is too small, it will be difficult for the solution to enter the interior of the fiber and the drug will be difficult to release into the medium, resulting in too low cumulative release in the later stage. On the contrary, if the proportion of hydrophobic polymers is too small and the proportion of hydrophilic polymers is too large, it will be difficult to maintain the fiber structure in the solution. At the same time, when the hydrophilic part of the outer layer is dissolved, the solution contacts the interior of the fiber over a large area, which will lead to a sudden release phenomenon in the later stage of release.

[0027] As a preferred solution, in step 2), the solvent is composed of at least one of dichloromethane and chloroform and water. The present invention selects dichloromethane and chloroform as solvents because they have good solubility for hydrophobic polymer materials and are easy to volatilize. After being prepared into drug-loaded nanofibers, they can be removed by physical drying without interfering with the drug-loaded system; but they have a low dielectric constant, which will lead to difficulties in continuous fiber production and a wide distribution of fiber diameters. In order to improve the uniformity of the fiber, the present invention introduces a non-solvent-water to form a polymer / solvent / non-solvent ternary system. In this system, water has a higher boiling point and a higher dielectric constant than the solvent, and thus can promote fiber production and fiber uniformity and porosity. It is further preferred that dichloromethane and water are composed in a volume ratio of (20-40):1.

[0028] As a preferred solution, in step 3), the conditions for electrospinning are: using a spinning needle of 18 to 22G, a needle voltage of 18 to 25 kV, a receiving distance of 15 to 18 cm, a spinning solution propulsion speed of 0.5 to 1.0 ml / h, and a receiving drum speed of 800 to 1000 r / min.

[0029] As a preferred solution, in step 4), the drying temperature is 40-50° C., the drying time is 4-6 hours, and after drying, the obtained porous drug-loaded sustained-release nanofiber membrane is sealed and stored in a light-proof and dry environment for future use.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1) The present invention adopts electrospinning technology, which is simple to operate and has controllable parameters; biodegradable polymer materials are selected, the materials are easy to obtain, and the reaction conditions are mild.

[0032] 2) The present invention adopts zeolite modification to prepare porous nanofibers as drug carriers, so that the drug is first loaded on the zeolite and then wrapped inside the nanofibers, and the introduction of zeolite can form a uniform porous structure on the surface of the nanofibers. The formation of this structure can make the drug diffuse through multiple paths, effectively extending the sustained release time. First, the water-soluble drugs dispersed in the inside of the nanofibers are quickly released by the dissolution of the hydrophilic polymer, then the drugs loaded on the zeolite surface are released through the pore structure of the fiber, and finally the drugs adsorbed in the zeolite holes are slowly released. The material of the present invention not only realizes the function of sustained release, avoids the side effects of sudden release of drugs, reduces the number of drug administration, but also can realize the control of drug usage by cutting the nanofibers, thereby improving the safety of medication.

[0033] 3) The drug-carrying polymer selected in the present invention is biodegradable and biocompatible, which not only provides a certain hydrophobicity to the drug-carrying system to ensure the stability of the drug-carrying stent, but also provides a certain hydrophilicity to ensure the combination of the drug and the polymer, which can effectively improve the absorption and volatilization effect of the drug in the organism and optimize the drug administration method.

[0034] 4) The present invention uses dichloromethane, chloroform and water as solvents in the spinning solution to form a polymer / solvent / non-solvent ternary system, which can not only form a porous structure on the surface of the nanofiber through volatilization, but also utilize the high dielectric constant of water to promote fiber production and fiber uniformity and porosity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Examples 1 to 8 of the present invention and comparative examples 1 to 2 (corresponding to Figure 1 (a)~ Figure 1 (j)) SEM image of the prepared porous nanofibers.

[0036] Figure 2 This is a comparison chart of the in vitro release of drug-loaded nanofibers prepared in Examples 1 to 8 of the present invention and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0039] The zeolite used in the examples and comparative examples of the present invention is stellerite mined in Chetian Township, Guangxi.

[0040] Example 1

[0041] A method for preparing stilbene-modified porous drug-loaded sustained-release nanofibers includes preparing the fibers by electrostatic spinning technology and testing the sustained-release performance.

[0042] The electrospinning method described above is used to prepare stellerite-modified porous drug-loaded sustained-release nanofibers as follows:

[0043] (1) Preparation of drug-loaded zeolite: Diclofenac sodium and 5000 mesh stellerite were dispersed in water at a mass ratio of 1:1, ultrasonicated at 37° C. to make them uniformly dispersed, and then stirred at 80° C. until the water was completely evaporated to obtain drug-loaded zeolite powder;

[0044] (2) Spinning solution preparation: Dissolve hydrophobic polymer PLA in 35 mL of dichloromethane and hydrophilic polymer PVA in 1 mL of water, stir at 37°C to make them completely mixed, and then add the above-mentioned drug-loaded zeolite powder until the zeolite powder is evenly dispersed in the polymer solution. The total mass concentration of PLA and PVA is 12%, the mass ratio is 1:0.1, and the mass concentration of the drug-loaded zeolite is 4%.

[0045] (3) Preparation of porous nanofiber membrane: The spinning solution was taken into a 10 ml syringe and a 20G needle was used for electrospinning. The syringe was fixed to a propulsion pump and pushed at a speed of 0.8 ml / h. A 25 kV high voltage electric field was applied between the syringe needle tip and the receiver, and the receiving distance was 15 cm. At the same time, the receiver rotated at a speed of 1000 r / min. After spinning, drug-loaded nanofibers were obtained.

[0046] (4) Sample collection: The drug-loaded nanofibers were placed in an oven at 45°C for 5 h and then sealed and stored at room temperature away from light for later use.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that the mass ratio of diclofenac sodium to stellerite is changed to 1:2, and the other conditions and steps are the same.

[0049] Example 3

[0050] The only difference between this embodiment and embodiment 1 is that the mass ratio of diclofenac sodium to stellerite is changed to 1:3, and the mass concentration of the drug-loaded zeolite in the spinning solution is 5%, and the other conditions and steps are the same.

[0051] Example 4

[0052] The only difference between this embodiment and embodiment 1 is that the mesh size of stellerite is changed to 10000 mesh, and the other conditions and steps are the same.

[0053] Example 5

[0054] The only difference between this embodiment and embodiment 2 is that the mesh size of stellerite is changed to 10000 mesh, and the other conditions and steps are the same.

[0055] Example 6

[0056] The difference between this embodiment and embodiment 1 is that the mesh size of stellerite is changed to 1250 mesh, and the other conditions and steps are the same.

[0057] Example 7

[0058] A method for preparing stilbene-modified porous drug-loaded sustained-release nanofibers includes preparing the fibers by electrostatic spinning technology and testing the sustained-release performance.

[0059] The electrospinning method described above is used to prepare stellerite-modified porous drug-loaded sustained-release nanofibers as follows:

[0060] (1) Preparation of drug-loaded zeolite: Diclofenac sodium and 1250 mesh zeolite were dispersed in water at a mass ratio of 1:2, ultrasonicated at 37°C to make them uniformly dispersed, and then stirred at 90°C until the water was completely evaporated to obtain drug-loaded zeolite powder;

[0061] (2) Preparation of spinning solution: Dissolve hydrophobic polymer PLA in 30 mL of dichloromethane and hydrophilic polymer PVA in 1.5 mL of water, stir at 37°C to make them completely mixed, and then add the above-mentioned drug-loaded zeolite powder until the zeolite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 8%, the mass ratio is 1:0.3, and the mass concentration of the drug-loaded zeolite is 5%.

[0062] (3) Preparation of porous nanofiber membrane: The spinning solution was drawn into a 10 ml syringe and a 20G needle was used for electrospinning. The syringe was fixed to a propulsion pump and pushed at a speed of 0.5 ml / h. An 18 kV high voltage electric field was applied between the syringe needle tip and the receiver, with a receiving distance of 15 cm. At the same time, the receiver rotated at a speed of 1000 r / min. After spinning, drug-loaded nanofibers were obtained.

[0063] (4) Sample collection: The drug-loaded nanofibers were placed in an oven at 50°C for 5 h and then sealed and stored at room temperature away from light for later use.

[0064] Example 8

[0065] The only difference between this embodiment and embodiment 2 is that the mass concentration of the drug-loaded zeolite in the spinning solution is changed to 3%, and the other conditions and steps are the same.

[0066] Comparative Example 1

[0067] An electrospinning method is used to prepare drug-loaded sustained-release nanofibers. The difference between this comparative example and Example 1 is that no stellerite is added.

[0068] (1) Preparation of spinning solution: Dissolve hydrophobic polymer PLA in dichloromethane, dissolve hydrophilic polymer PVA in 1 mL of water, stir at 37°C to make them completely mixed, and then add diclofenac sodium to disperse evenly in the polymer solution. The total concentration of PLA and PVA is 12%, the mass ratio is 1:0.1, and the mass concentration of diclofenac sodium is 2% (wherein the drug concentration is consistent with that in Example 1).

[0069] (2) Preparation of porous nanofiber membrane: The spinning solution was taken into a 10 ml syringe and a 20G needle was used for electrospinning. The syringe was fixed to a propulsion pump and pushed at a speed of 0.8 ml / h. A 25 kV high voltage electric field was applied between the syringe needle tip and the receiver, and the receiving distance was 15 cm. At the same time, the receiver rotated at a speed of 1000 r / min. After spinning, drug-loaded nanofibers were obtained.

[0070] (3) Sample collection: The drug-loaded nanofibers were placed in an oven at 45°C for 5 h and then sealed and stored at room temperature away from light for later use.

[0071] Comparative Example 2

[0072] The only difference between this comparative example and Example 1 is that no water is added to the spinning solution, and the other conditions and steps are the same.

[0073] The in vitro release experiment of the drug-loaded nanofibers obtained in Examples 1 to 8 and Comparative Examples 1 to 2 was specifically conducted as follows: a certain volume of drug-loaded nanofibers was placed in a PBS release medium with a pH of 7.2 to 7.4, and placed in a constant temperature shaker, and the setting conditions were 37°C and 100 r / min. Samples were taken at a certain time point, and an equal volume of PBS solution at the same temperature was replenished at the same time. The in vitro cumulative release of the drug was tested using a UV-visible spectrophotometer.

[0074] Depend on Figure 1 (a-c, h) It can be seen that when the zeolite powder is 5000 mesh, the pores increase significantly with the increase of the amount of stilbene zeolite, but when the ratio of drug to stilbene zeolite is 1:3, the uniformity of the nanofiber pore size decreases. Figure 1 (d-e) It can be seen that when the zeolite powder is 10000 mesh, the diameter and pore size of the nanofibers are significantly reduced. Figure 1 (fg) It can be seen that when the zeolite powder is 1250 mesh, the diameter and pore size of the nanofibers increase significantly, which indicates that the diameter and pore size of the nanofibers are related to the coarseness of the zeolite powder. Figure 1(i) is the nanofiber without zeolite. It can be seen from the figure that the pores of the nanofiber are unevenly distributed and only distributed on the shallow surface of the fiber, which is not conducive to the release of the drug; Figure 1 (j) is the nanofiber without adding water, Figure 1 (j) It can be found that when no water is added to the spinning solution, the size of the nanofibers is not uniform due to the low dielectric constant and poor conductivity of the solvent.

[0075] Depend on Figure 2 It can be seen that, for Examples 1 to 3, the release rates in the early stage are similar, and at this time, the drugs on the surface of the nanofibers are mainly released. In the middle and late stages of sustained release, compared with Example 2, Example 1 has slightly more drugs loaded in Example 1, and more drugs are adsorbed on the surface of the zeolite and in the mesopores, so the release rate and cumulative release rate are high. Compared with Example 3, although the ratio of drug to zeolite is reduced, the amount of drug-loaded zeolite is increased, and the pores in Example 3 are significantly larger than those in Example 1, so the sustained release of Example 3 is slightly faster than that of Example 1. Examples 6 and 7 are 1250 mesh zeolites, and compared with 5000 mesh zeolites in Example 1 and 10000 mesh zeolites in Example 4 and Example 5, the fiber size and pore size are significantly increased. Due to the larger pore size, the early release rate is significantly better than that of Example 1, but due to the larger diameter and the larger zeolite particle size, the drugs inside the fibers and zeolite particles are not easy to be released in the middle and late stages of sustained release, so the later release rate and cumulative release rate are relatively low. In Example 4 and Example 5, the zeolite particle size is too small, and the amount of drug loaded in the mesopores is small, resulting in almost no release in the middle and late stages of sustained release. However, overall, the cumulative release rate of Examples 1 to 8 is significantly better than that of Comparative Examples 1 to 2, which improves the utilization rate of the drug. Moreover, in the first hour of sustained release, the drug release rate of Examples 1 to 8 is better than that of Comparative Examples 1 to 2, mainly because the nanofibers in Examples 1 to 8 have more pore structures (such as Figure 1 As shown), a path is provided for the early release of the drug. After 250 minutes, the sustained release rate of the embodiment slows down and the drug is slowly released. This is because the drug adsorbed in the mesopores of the stellerite is released, which effectively prolongs the release time of the drug.

Claims

1. A zeolite-modified porous drug-loaded sustained-release nanofiber, characterized in that: It is composed of zeolite, water-soluble drugs and nanofibers with a porous structure; wherein the zeolite is wrapped inside the nanofibers, and the water-soluble drugs are loaded in the mesopores of the zeolite and on its surface and inside the nanofibers; The nanofiber comprises a hydrophilic polymer material and a hydrophobic polymer material.

2. The zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 1, characterized in that: The pore size range of the porous structure on the surface of the nanofiber is 10-200 nm.

3. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 1 or 2, characterized in that: The following steps are involved: 1) dispersing a water-soluble drug and zeolite in water and then mixing and stirring until the water is completely volatilized to obtain drug-loaded zeolite powder; the zeolite has a mesoporous structure; 2) dissolving a hydrophilic polymer material and a hydrophobic polymer material in a solvent and mixing the solvent with drug-loaded zeolite powder to obtain a spinning solution; 3) Absorb the spinning solution for electrostatic spinning, and then dry it to obtain the product.

4. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 3, characterized in that: The water-soluble drug includes any one of diclofenac sodium and sodium valproate; The mass ratio of the water-soluble drug to the zeolite is 1:(1-5).

5. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 4, characterized in that: The particle size of the zeolite is 1250-10000 meshes.

6. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 3, characterized in that: The mass concentration of the drug-loaded zeolite powder in the spinning solution is 2-5%.

7. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to any one of claims 4 to 6, characterized in that: In step 1), the mixing and stirring temperature is 50-90°C.

8. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 3, characterized in that: The total mass concentration of the hydrophilic polymer material and the hydrophobic polymer material in the spinning solution is 8-12%; The hydrophilic polymer material includes at least one of PVP and PVA; The hydrophobic polymer material includes at least one of PLA and PCL.

9. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 8, characterized in that: The mass ratio of the hydrophobic polymer material to the hydrophilic polymer material is (10-1):

1.

10. The method for preparing a zeolite-modified porous drug-loaded sustained-release nanofiber according to claim 9, characterized in that: In step 2), the solvent is composed of at least one of dichloromethane and chloroform and water; In step 3), the electrospinning conditions are: using a spinning needle of 18-22G, a needle voltage of 18-25kV, a receiving distance of 15-18cm, a spinning solution propulsion speed of 0.5-1.0ml / h, and a receiving drum speed of 800-1000r / min.

Citation Information

Cited By

  • Corrosion-resistant water-based paint and preparation process thereof

    CN120349696A